Collective Efficacy and Co-Teaching Relationships in Inclusive Classrooms - Pizana, Ruby F. (Future Science / FSH-PH Publications, 2022)
Co-teaching is becoming prevalent in meeting the needs of students with disabilities in the general education classroom. Co-teachers face more challenges in collaboration, relationships, and defining roles. Collective teacher efficacy is the shared belief that a team of co-teachers can make a positive difference in student achievement and school culture. This quantitative study aims to assess the teachers' self-efficacy and the collective efficacy of the co-teaching team to develop cohesive and working relationships to benefit students in inclusive middle classrooms in a suburban school district in the United States. Bandura’s (1977) social cognitive theory and efficacy as a set of proximal determining factors of teachers’ affect and actions theoretically framed the study. The research questions used focused on understanding the kinds of things that create challenges for teachers. Also, they considered the combination of the current ability, resources, and opportunities for teachers and the co-teaching team. The data from the instruments were collected, categorized, and tabulated for interpretation and analysis. The findings show correlated efficacy factors in student engagement, instructional practices, and classroom management. The results recommended for same planning time, collaboration, and understanding of shared roles of the co-teaching team.